2016
DOI: 10.1371/journal.pone.0164945
|View full text |Cite
|
Sign up to set email alerts
|

Light Effects on Behavioural Performance Depend on the Individual State of Vigilance

Abstract: Research has shown that exposure to bright white light or blue-enriched light enhances alertness, but this effect is not consistently observed in tasks demanding high-level cognition (e.g., Sustained Attention to Response Task—SART, which measures inhibitory control). Individual differences in sensitivity to light effects might be mediated by variations in the basal level of arousal. We tested this hypothesis by measuring the participants’ behavioural state of vigilance before light exposure, through the Psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 38 publications
(64 reference statements)
1
20
1
Order By: Relevance
“…Exposure to blue-enriched light has been proposed as a resource for enhancing alertness and cognitive performance in adverse circumstances, such as at nighttime ( Lockley et al, 2006 ; Phipps-Nelson et al, 2009 ; Chellappa et al, 2011 ; Kretschmer et al, 2011 ; Taillard et al, 2012 ; Correa et al, 2016 ) or after sleep restriction ( Phipps-Nelson et al, 2003 ; Gabel et al, 2013 , 2015 ). Cognitive effects of light have been studied also during daytime ( Vandewalle et al, 2006 , 2007 , 2011 ; Huiberts et al, 2015 ; Smolders and de Kort, 2017 ), but its influence in extreme chronotypes performing at their suboptimal time of day had not been addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to blue-enriched light has been proposed as a resource for enhancing alertness and cognitive performance in adverse circumstances, such as at nighttime ( Lockley et al, 2006 ; Phipps-Nelson et al, 2009 ; Chellappa et al, 2011 ; Kretschmer et al, 2011 ; Taillard et al, 2012 ; Correa et al, 2016 ) or after sleep restriction ( Phipps-Nelson et al, 2003 ; Gabel et al, 2013 , 2015 ). Cognitive effects of light have been studied also during daytime ( Vandewalle et al, 2006 , 2007 , 2011 ; Huiberts et al, 2015 ; Smolders and de Kort, 2017 ), but its influence in extreme chronotypes performing at their suboptimal time of day had not been addressed.…”
Section: Discussionmentioning
confidence: 99%
“…To date, multiple studies have investigated diurnal acute non–image forming (NIF) effects of light intensity on alertness (e.g., Badia et al, 1991 ; Daurat et al., 1993 ; Huiberts et al, 2015 , 2016 ; Phipps-Nelson et al, 2003 ; Rüger et al, 2006 ; Vandewalle et al, 2006 ), complementing a large body of research on the nocturnal effects of light on alertness (e.g., Cajochen et al, 2000 ; Dijk et al, 1991 ; Chellappa et al, 2013 ; Correa et al, 2016 ; Figueiro et al, 2007 ; Lavoie et al, 2002 ; Lockley et al, 2006 ; Myers and Badia, 1993 ). While there are indications that light may induce acute alertness-enhancing effects during daytime, the current findings on subjective and objective indicators of alertness are inconclusive, as some studies reported beneficial effects while others reported no significant light-induced modulations in alertness (for reviews, see Lok et al, 2018a [this issue]; Souman et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…These cells transmit signals to hypothalamic nuclei, which in turn regulate the production of melatonin ( 16 , 17 ). Morning exposure to blue wavelength light leads to a suppression of melatonin production, which contributes to a phase delay and stabilization of the circadian rhythm ( 18 ), increases daytime alertness and vigilance, and earlier onset of evening sleep ( 19 , 20 ). Interestingly, a recent clinical trial showed that 4 weeks of 45 min of morning blue-light therapy (BLT) in comparison to longer wavelength placebo light was effective at reducing self-rated fatigue and daytime sleepiness among individuals recovering from TBI ( 21 ).…”
Section: Introductionmentioning
confidence: 99%